HOW 'DEEP' IS YOUR BRAND? The Hierarchical Effects Model of Emotional Branding - Wijaya, Bambang Sukma (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2013)
This article elucidates the depth of consumer affection with a brand through a hierarchy of branding called the AKIELS Model. From the initial stage of consumer exposure in Brand Awareness continues to the consumer understanding of the values ​​and attributes in Brand Knowledge. The next step is the Brand Image. Consumers get a specific image and imagination about a brand, then the Brand Experience stage, where consumers touch the 'reality' offered by the brand. If consumers' reality is positive, then the next step is Brand Loyalty. Consumers begin to invest their emotional ties in an ongoing relationship. The deeper the relationship exists, the stronger the consumer's affective capital in a brand, so that the brand becomes one of the essential parts of a consumer's life. The brand becomes an ideological pleasure. The brand becomes a 'religion' that is maintained, obeyed, and consumers share its values to attract other consumers to join the circle of brand ideology that they hold. This stage is where the brand achieves the most profound meaning and the deepest position at the level of consumer affection, namely Brand Spirituality. AKIELS model of branding hierarchy can be a strategic tool to measure brand performance in its relationship with consumers. SEBERAPA 'DALAM' MEREK ANDA? Model Efek Hirarkis Pemerekan EmosionalArtikel ini menjelaskan kedalaman afeksi konsumen terhadap suatu merek melalui hierarki pemerekan yang disebut Model AKIELS. Dari tahap awal keterpaparan konsumen dalam Brand Awareness berlanjut ke pemahaman konsumen tentang nilai dan atribut merek dalam Brand Knowledge. Langkah selanjutnya adalah Brand Image. Konsumen mendapatkan gambaran dan imajinasi tertentu tentang suatu merek, kemudian tahap Brand Experience, di mana konsumen menyentuh 'realitas' yang ditawarkan merek tersebut. Jika realitas konsumen positif, maka langkah selanjutnya adalah Brand Loyalty. Konsumen mulai menginvestasikan ikatan emosional mereka dalam hubungan yang berkelanjutan. Semakin dalam hubungan tersebut terjalin maka semakin kuat modal afektif konsumen dalam suatu merek, sehingga merek tersebut menjadi salah satu bagian esensial dalam kehidupan konsumen. Merek menjadi kesenangan ideologis. Merek menjadi 'agama' yang dijaga, ditaati, dan konsumen pun berbagi nilai-nilai merek yang dirasakannya untuk menarik konsumen lain bergabung dalam lingkaran ideologi merek yang mereka pegang. Tahap ini adalah saat merek mencapai makna yang paling dalam dan posisi tertinggi pada tingkat afeksi konsumen, yakni tahap pamungkas Brand Spirituality. Model AKIELS dalam hirarki branding dapat menjadi perangkat strategis untuk mengukur kinerja merek dalam hubungannya dengan konsumen. To cite this article (7th APA style):Wijaya, B. S. (2013). How ‘Deep’ is Your Brand? The Hierarchical Effects Model of Emotional Branding. Journal Communication Spectrum, 3(2), 158-169. https://doi.org/10.36782/jcs.v3i2.1974